2008
DOI: 10.1007/s11695-008-9472-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surgical Weight Loss on Sleep Architecture in Adolescents with Severe Obesity

Abstract: Our data demonstrate a marked improvement in sleep efficiency and sleep fragmentation with surgical weight loss. Given the emerging evidence that surgical weight loss results in resolution of obesity-associated psychosocial, metabolic, and cardiovascular morbidity, these results suggest that correction of sleep fragmentation could be an important but as yet underappreciated factor influencing changes in these other major comorbidities of obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 31 publications
3
25
0
Order By: Relevance
“…[47][48][49] Conversely, interventions aiming to reduce the degree of adiposity have also been associated with improvements in OSA. 50,51 In summary, the present study conclusively demonstrates that for any level of OSA severity the habitually snoring obese child requires less adenotonsillar hypertrophy when compared to nonobese children of the same age, gender, and ethnicity. These differences appear to be mediated, at least in part, by the presence of a more crowded airway in obese children, as a corollary to increased fat deposits in the airway.…”
Section: Discussionsupporting
confidence: 65%
“…[47][48][49] Conversely, interventions aiming to reduce the degree of adiposity have also been associated with improvements in OSA. 50,51 In summary, the present study conclusively demonstrates that for any level of OSA severity the habitually snoring obese child requires less adenotonsillar hypertrophy when compared to nonobese children of the same age, gender, and ethnicity. These differences appear to be mediated, at least in part, by the presence of a more crowded airway in obese children, as a corollary to increased fat deposits in the airway.…”
Section: Discussionsupporting
confidence: 65%
“…16 In addition to consistently lowering AHI, weight loss following surgery has been reported to improve nocturnal sleep architecture. [13][14][15] This includes decreasing stage 1 sleep, and increasing the expression of stage 2 sleep, REM sleep, and SWS. [13][14][15] Since in each case, body weight and AHI were concomitantly reduced after surgery, it is unclear which is driving these favorable changes in sleep: the weight loss or the improved AHI.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] This includes decreasing stage 1 sleep, and increasing the expression of stage 2 sleep, REM sleep, and SWS. [13][14][15] Since in each case, body weight and AHI were concomitantly reduced after surgery, it is unclear which is driving these favorable changes in sleep: the weight loss or the improved AHI. Current results indicate that the improvements in stage 1, stage 2, and REM sleep, are more likely to be influenced by the reduction in OSA severity than by the loss of body weight per se.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although definitive studies are underway, many have shown that surgery in adolescents results in improvement or resolution of numerous comorbid conditions including sleep apnea, 312 diabetes 313 and improvement in quality of life. 314,315 Perioperative and longer term risks must be acknowledged, 309,316 and bariatric surgery among severely obese adolescents is a viable option, 317,318 but further research is required to determine the long-term effectiveness of this approach.…”
Section: Bariatric Surgery For Obesity and Risk Factor Reduction In Pmentioning
confidence: 99%